2020
DOI: 10.3389/fpsyg.2020.578378
|View full text |Cite
|
Sign up to set email alerts
|

‘When They Struggle, I Cannot Sleep Well Either’: Perceptions and Interactions Surrounding University Student and Teacher Well-Being

Abstract: A wealth of evidence has indicated that both students and teachers experience high levels of stress, burnout, and ultimately compromised well-being in the university context. Although numerous studies have investigated well-being among university students, and other studies have addressed well-being among university teachers, these lines of research are often conducted in isolation from one another. This is surprising, as the importance of considering reciprocal links between students and teachers has been sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 85 publications
1
26
0
Order By: Relevance
“…Consequently, teachers with such a focus can be expected to have a desire to succeed, put forth effort, and have successful experiences in teaching that contribute to positive emotions as well as job and life satisfaction. This coincides with findings by Kiltz et al (2020), where university teachers felt that their commitment to succeed in their teaching activities was interwoven with their well-being. Similarly, documented that task approach goals had the most advantageous associations with teaching-related outcomes, including positive affect.…”
Section: Mastery Approach and Avoidance Goalssupporting
confidence: 88%
See 1 more Smart Citation
“…Consequently, teachers with such a focus can be expected to have a desire to succeed, put forth effort, and have successful experiences in teaching that contribute to positive emotions as well as job and life satisfaction. This coincides with findings by Kiltz et al (2020), where university teachers felt that their commitment to succeed in their teaching activities was interwoven with their well-being. Similarly, documented that task approach goals had the most advantageous associations with teaching-related outcomes, including positive affect.…”
Section: Mastery Approach and Avoidance Goalssupporting
confidence: 88%
“…In addition, it should be acknowledged that just as student-teacher interactions have the potential to be adaptive for aspects of higher education teachers' SWB, they can also be maladaptive. This has also been recognized by Kiltz et al (2020), who found that the student-teacher relationship was frequently mentioned to be important by university instructors, both in a positive and in a negative light.…”
Section: Relational Goalsmentioning
confidence: 63%
“…On the other hand, it is possible that personal acquaintance helped both sides to be more open in the interview situation. The sample size of n = 30 might appear small, but is average for qualitative research among university students [ 25 , 26 , 27 , 28 ]. Due to the qualitative approach, our results are not generalizable in a statistical way, but they deliver valuable subjective insight from different perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…With the substantial effect of societal restrictions on people's life, the COVID-19 pandemic has affected overall well-being, including social, emotional, physical, and psychological facets (e.g. González-Sanguino et al, 2020; for a thorough definition of student well-being, see Kiltz et al, 2020;World Health Organization, 2020). Taylor (2019) identifies various pandemic-related stressors associated with well-being, including uncertainty, disruption of routines, separation from family, social isolation, financial insecurity, and closure of educational institutions.…”
Section: Student Well-being In Pandemic Timesmentioning
confidence: 99%
“…Competence relates to giving constructive feedback, and relatedness stems from investing in a respectful, appreciative relationship (Kiltz et al, 2020;Niemiec & Ryan, 2009). Moreover, student involvement and teacher support enhance the positive LE perception, resulting in higher life satisfaction (Zandvliet et al, 2019).…”
Section: Learning Environment and Basic Psychological Needsmentioning
confidence: 99%